2015
DOI: 10.31018/jans.v7i1.580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different modules for the management of tomato fruit borer, Helicoverpa armigera pest of tomato

Abstract: Among, six modules tested against Helicoverpa armigera on tomato, the IPM module I consisting interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot and spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of the first instar larvae.IPM module II was interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…64, 13.94, 34.20 and 111.8-fold resistance to fenvalerate, deltamethrin, cypermethrin and alphamethrin, respectively. Many other workers reported the high level of resistance to fenvalerate acquired by this pest from India as well as from other parts of the world (Gunning and Easton 1994, Armes et al 1992, Kranthi 1997, 2001, Chaturvedi 2013. Kranthi et al (2001) also observed in field populations of H. armigera high level of resistance to deltamethrin (24.21 to 69 fold) from Amravathi and Akola region of Maharashtra.…”
Section: Pair Wise Correlations Between Log Lc 50 Values Of Different...mentioning
confidence: 99%
See 1 more Smart Citation
“…64, 13.94, 34.20 and 111.8-fold resistance to fenvalerate, deltamethrin, cypermethrin and alphamethrin, respectively. Many other workers reported the high level of resistance to fenvalerate acquired by this pest from India as well as from other parts of the world (Gunning and Easton 1994, Armes et al 1992, Kranthi 1997, 2001, Chaturvedi 2013. Kranthi et al (2001) also observed in field populations of H. armigera high level of resistance to deltamethrin (24.21 to 69 fold) from Amravathi and Akola region of Maharashtra.…”
Section: Pair Wise Correlations Between Log Lc 50 Values Of Different...mentioning
confidence: 99%
“…These pests cause damage to the aerial parts of the tomato plant from the very early growth till to the fruit maturation stage (Tripathy and Singh 1999) and results in yield loss ranged from 12.9 to 54.82% (Kaur et al 2011). The loss incurred to growing tomato crop is insurmountable and may extend up to 63.20% in Punjab (Kaur 2001). Apart from tomato, the pest is reported to infest cotton, maize, chickpea, pigeon pea, sorghum, sunflower, soybean, and groundnut and hence has attained the national importance as key pest (Yaqoob and Arora 2005).…”
mentioning
confidence: 99%